2001
DOI: 10.17221/6582-cjfs
|View full text |Cite
|
Sign up to set email alerts
|

The relationships between the chemical, dielectric and sensory properties of Edam cheese during ripening

Abstract: Proteolysis, dielectric properties and sensory data were measured during ripening of Edam type cheese (30% and 45% FDM). Cheese of different age (1-25 weeks) was analysed. Dielectric properties were used as a method for assessing proteolysis. Permitivity had significantly similar continuance as pH 4.4 total soluble N, both in opposite to sweet milky taste, during ripening period. This paper offers dielectric properties as useful characteristics for assessing proteolysis in cheese.Keywords: Edam cheese; proteol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
3
0

Year Published

2006
2006
2019
2019

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 9 publications
1
3
0
Order By: Relevance
“…No more statistic differences in hardness between the surface and centre of the Edam cheeses have been found in further months. Similar results are confirmed by the research works Kubiš et al (2013). Hardness in the mouth had a similar course as the hardness between fingers.…”
Section: Resultssupporting
confidence: 91%
“…No more statistic differences in hardness between the surface and centre of the Edam cheeses have been found in further months. Similar results are confirmed by the research works Kubiš et al (2013). Hardness in the mouth had a similar course as the hardness between fingers.…”
Section: Resultssupporting
confidence: 91%
“…The cheeses were evaluated organoleptically by a team of experienced cheese graders. The cheeses were graded for appearance (5 points), body and texture (holes, color and consistency) (5 points), aroma (3 points) and taste (8 points) according to Kubis et al, (2001).…”
Section: Methodsmentioning
confidence: 99%
“…Factors such as physical state, water-holding capacity of proteins, history of time-temperature exposure, and denaturation of proteins can influence the dielectric properties of protein rich samples (Bircan, et al, 2001). Also, a steady increase in ε′ and a decrease in ε″ was observed by Kubiš et al (2001) during ripening of Edam cheese. Datta et al (2005) reported that proteins are relatively less reactive to microwave frequencies.…”
Section: Dielectric Spectra Of Pcmentioning
confidence: 99%
“…The type, quantity, and age of natural cheese in a PC formulation affect the dielectric properties as well as the functional properties of PC. As the intact CN and mineral content of PC is a significant contributor to its functionality as well as dielectric properties (Kubiš et al, 2001), we hypothesized that dielectric spectroscopy can provide a rapid and noninvasive method of determining the texture and melting characteristics of PC.…”
Section: Introductionmentioning
confidence: 99%